THE EFFECT OF COCONUT COIR FIBER POWDER CONTENT AND HARDENER WEIGHT FRACTIONS ON MECHANICAL PROPERTIES OF AN EPR-174 EPOXY RESIN COMPOSITE - Muhamad Fitri; Shahruddin Mahzan; Imam Hidayat; Nurato Nurato (SINERGI, 2021)
The development of composite materials is increasingly widespread, which require superior mechanical properties. From many studies, it is found that the mechanical properties of composite materials are influenced by various factors, including the reinforcement content, both in the form of fibers and particle powder. However, those studies have not investigated the effect of the hardener weight fraction on the mechanical properties of resin composite materials. Even though its function as a hardener is likely to affect its mechanical properties, it might obtain the optimum composition of the reinforcing content and hardener fraction to get the specific mechanical properties. This study examines the effect of hardener weight fraction combined with fiber powder content on mechanical properties of EPR-174 epoxy resin matrix composite and determines the optimum of Them. The research was conducted by testing a sample of composite matrix resin material reinforced with coconut fiber powder. The Powder content was made in 3 levels, i.e.: 6%, 8%, and 10%. While the hardener fraction of resin was made in 3 levels, i.e.: 0.4, 0.5, and 0.6. The test results showed that pure resin had the lowest impact strength of 1.37 kJ/m2. The specimen with a fiber powder content of 6% has the highest impact strength i.e.: 4.92 kJ/m2. The hardener fraction of 0.5 has the highest impact strength i.e.: 4.55 kJ/m2. The fiber powder content of 8% produced the highest shear strength i.e.: 1.00 MPa. Meanwhile, the hardener fraction of 0.6 has the highest shear strength i.e.: 2.03 MPa.